IMPLEMENTASI PROBLEM BASED LEARNING BERBASIS TEACHING AT THE RIGHT LEVEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS 5 - Ferdianti, Cindy Ineke; Diputri, Silvia Ratna Dewi; Nurtamam, Mohammad Edy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Student learning outcomes in the Indonesian language subject indicate the need for more effective learning strategies to enhance language comprehension and skills.The Merdeka Curriculum emphasizes flexible learning and the Teaching at The Right Level (TaRL) strategy, which adjusts the learning process to the actual abilities of the students.The Problem Based Learning (PBL) model can encourage students to think critically, collaborate, and find solutions relevant to their lives.This study aims to obtain information regarding the differences in learning outcomes of fifth-grade students on the topic of imperative sentences using the PBL learning model with the TaRL approach.This research is classified as Classroom Action Research (CAR) conducted in two cycles.In the pre-cycle, an initial test was conducted to determine the students' learning outcomes.The subjects in this study are 28 fifth-grade students at SD Negeri Banyuajuh 3 Kamal.From the initial test results, the average learning outcomes of the students were 64,28, and the achievement of student learning completeness was 46.43%.In cycle 1, the average score and student learning increased to 73,92, and the achievement of student learning completeness was 60,71%.In cycle 2, the average learning score of the students was 86,78, and the achievement of student learning completeness was 85,71%.Therefore, it can be concluded that the application of the PBL learning model combined with the TaRL approach is capable of improving students' learning outcomes.